2019
DOI: 10.3390/cancers11111803
|View full text |Cite
|
Sign up to set email alerts
|

CD147 Is a Promising Target of Tumor Progression and a Prognostic Biomarker

Abstract: Microenvironment plays a crucial role in tumor development and progression. Cancer cells modulate the tumor microenvironment, which also contribute to resistance to therapy. Identifying biomarkers involved in tumorigenesis and cancer progression represents a great challenge for cancer diagnosis and therapeutic strategy development. CD147 is a glycoprotein involved in the regulation of the tumor microenvironment and cancer progression by several mechanisms—in particular, by the control of glycolysis and also by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 124 publications
1
102
0
Order By: Relevance
“…However, effective immunotherapies, whether they are adoptive cell therapy or checkpoint blockade‐based approaches, have been limited for patients because of immunosuppressive barriers that exist in TME. The TME is known to be essential to the onset, development, progression, and relapse of many types of cancers 27 . Thus, deeper explorations of the complexities within the TME may help to reveal novel biomarkers that could facilitate increased accuracy of prognosis for patients and their potential responsiveness to immunotherapy as well as improve therapeutic modulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, effective immunotherapies, whether they are adoptive cell therapy or checkpoint blockade‐based approaches, have been limited for patients because of immunosuppressive barriers that exist in TME. The TME is known to be essential to the onset, development, progression, and relapse of many types of cancers 27 . Thus, deeper explorations of the complexities within the TME may help to reveal novel biomarkers that could facilitate increased accuracy of prognosis for patients and their potential responsiveness to immunotherapy as well as improve therapeutic modulation.…”
Section: Discussionmentioning
confidence: 99%
“…The potential involvement of tumor-derived sEVs in the process of CR-CSC differentiation is also poorly understood and may be a key point to explore given that the differentiation of CR-CSC could be an attractive therapeutic strategy. Dai et al demonstrated that subpopulations of tumor cell lines that constitutively express high levels of cell-surface CD147 exhibit cancer stem-like cell features and Yoshioka and colleagues confirmed a high level of CD147 expression in EVs isolated from CRC cell lines [13,33]. Despite the interest in CD147, its involvement in the differentiation of CR-CSC and in the effects of sEV on recipient cells has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…CD147 is a glycoprotein released by tumor cells and transferred to surrounding cells (both cancer cells and TME) in soluble form or by EVs [12]. CD147-sEVs have been identified in ovarian and bladder cancer, and recent evidence suggests that circulating CD147-containing EVs might be used as a biomarker to monitor response to therapy in CRC patients, but no study so far has analyzed the CD147 fate during colorectal cancer stem cell lines (CR-CSCs) differentiation [13][14][15][16]. This study aimed to analyze the role of sEVs in the differentiation process of CR-CSC and to understand whether CD147-sEVs could be involved in differentiation therapy inefficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, we found that CD147 could facilitate collective invasion. Previous studies have shown that CD147 promotes tumor cell adhesion, migration and invasion in various kinds of cancers [40] and the underlying mechanisms are diverse depending on the type of cancer and are not fully understood. We and others have found that enriched expression of CD147 on the surface of tumor cells induces stromal and tumor cells themselves to increase MMPs expression and secretion, leading to the degradation of the surrounding stroma [30,41].…”
Section: Discussionmentioning
confidence: 99%